Literature of Exile and Exile in Literature: Bosniaks in Turkey (Prilozi za orijentalnu filologiju, 2021)
The number of descendants of Bosniak migrants in Anatolia has led us to examine the issue of existence of literature of exile in this community; as well as the theme of Bosniak migration to Turkey in literary texts.This paper presents biographies of authors of Bosniak origin and indicates elements of literature of exile in their work: Mehmet Ruhi Turan (1900-1981); Ahmet Cemil Miroğlu – Asri (1907-1971); Memduh Cumhur (1947-2018); Cemil Kavukçu (1955- ); Yavuz Bubik (1940-). The corpus also includes the novels Gözüm Yaşı Tuna Selidir Şimdi by Selm Fındıklı and Cüda by Halil İbrahima Izgi – authors whose biographies include no information about their Bosniak ancestry; but their novels focus on migration of Bosniaks to Anatolia and Ottoman-governed Palestine.Stories about the circumstances that led to migration; about the trauma of leaving home; about otherness; identity; hopes for return; nostalgia – more than a century later; after the loss of even the Bosnian linguistic identity; speak through literary text in the Turkish language.